STUDIES ON BLOOD BIOCHEMICAL COMPOSITION OF POLLUTANT EXPOSED CRAB, PARATELPHUSA JACQUEMONTII (RATHBUN) - BHALE, K. B.; NIMGARE, S. S.; KAMATH, S. W.; KULKARNI, K. M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
As few pesticides like organophosphates are considered to be inhibitors of AchE, it could be concluded that the reduction in carbohydrate metabolism in treated crabs is due to general lowering of the metabolic activities There was increased protein breakdown to yield more energy to face the toxic impact. This was further corroborated through the increased levels of free amino acids. These free amino acids might be fed into TcA cycle as keto acids by way of transamination since transaninases are known to elevate during pesticide intoxication. The increased levels of amino acids might also be due to increased synthetic potentiality.